ANALISIS PERSEPSI KEPUASAN PENGGUNA LULUSAN FAKULTAS EKONOMI DAN BISNIS ISLAM INSTITUT AGAMA ISLAM SAHID BOGOR PERIODE 2015-2021 - Syaefudin; Thantawi, Tubagus Rifqy; Fadilah, Hafid (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2024)
This research is motivated by the influence of graduates of the Faculty of Economics and Islamic Business, Sahid Islamic Institute of Islam on the company. The purpose of this study was to analyze the influence of graduates of the Faculty of Economics and Islamic Business, Sahid Islamic Institute, Bogor. This research is qualitative and the method of data collection is by distributing questionnaires and by filling out questionnaires to colleagues from the graduates of the Faculty of Economics and Islamic Business, the Sahid Islamic Institute of Bogor, in their respective companies. The sample in this study were 40 people as respondents. There are several respondents who were included in the study, namely Gender, Place of Work, Position of Users of Graduates of the Faculty of Economics and Islamic Business, Sahid Islamic Institute Bogor, Year of Starting Work and Employment Status. To explain some of the respondents in question. This research shows that the analysis consisting of knowledge of the Faculty of Economics and Islamic Business Sahid Islamic Institute Bogor, simultaneously affects users of graduates of the Faculty of Economics and Islamic Business, Sahid Islamic Institute Bogor.